Meneroka kerangka analitikal teori sosiologi Max Weber dalam mengkaji pemikiran pembangunan Tun Dr. Mahathir Mohamad - Aziz, Khairul Azman; Mohd Noor, Mansor (Universiti Tun Hussein Onn Malaysia, 2013)
This paper provides an analytical framework of classical sociological theories of Max Weber (1864-1920) in the review of development thinking Tun Dr. Mahathir Mohamad as the leader of the country from 1981 to 2003. The theory that will be affected are 'social action theory', rational-legal and rational capitalism in reviewing ideas / thoughts and approach / policy development used in the period. The concept and features of the theory will be used to assess the rationale and approach of 'Mahathir factor' in making changes from the traditional to modern agriculture industry. It includes the successful development and policies to the folk- 'Mahathir generation'.Initial exploration on the thinking of Tun Dr. Mahathir is by assessing the value and value system that is positive towards development, rational thinking and approach towards efficient management of the organization. It is done by minimizing the cost, increase productivity, leadership, being systematic and discipline in pursuit of goals and ideas including rational-legal approach to bring solutions to the problems arise. However, the development of which is based on competition, market / market power and 'winners and losers' in the modernization approach will produce 'competitive individualism' that compete with the neglect of social values and community relations. To strengthen and sustain modern civilization, appropriate to Malaysian mold to religion / faith and spiritual paradigm through philosophical approach Islamic scholar al-Ghazali and Islam Hadhari towards stabilization of a civilized state by 2020.